Analysis of cellular and soluble profiles in QuantiFERON nonconverters, converters, and reverters in the Gambia - Lydia Medawar; Hatimi Mohd Tukiman; Georgetta Mbayo; Simon Donkor; Olumuyiwa Owolabi; Jayne S. Sutherland (Immunity, Inflammation and Disease, 2019)
Abstract Background Tuberculosis (TB) is the leading cause of death from a single infectious agent worldwide. The immune system is capable of clearing the pathogen before establishment of latent infection but the mechanisms for this are not yet understood. Methods This study analysed highly exposed household contacts (HHC) of TB index cases who were categorised according to QuantiFERON (QFT) results at recruitment and 6 months. Seventeen (17) QFT nonconverters, 14 QFT converters, 18 QFT reverters and 18 latent TB infection (LTBI) were analysed. Supernatants generated following QFT stimulation at both time‐points were analysed using a 64‐plex cytokine array. Flow cytometry was performed on QFT converters and nonconverters at baseline only. Results Interleukin‐2 (IL‐2), IL‐5, IL‐13, APRIL, IL‐17A, IP‐10, MIP‐1ß, sIL‐6rb, OPN, and sTNFR2 were all significantly higher in the QFT converters compared with nonconverters at baseline. Levels of interferon‐α2 (IFN‐α2) and IL‐2 were significantly lower in QFT reverters compared with nonconverters at baseline. Analysis of Ag‐specific IL‐2 levels resulted in an area under the curve (AUC) of 0.93 (95% confidence interval [CI], 0.84‐1.00) for QFT converters compared to nonconverters and an AUC of 0.80 (0.65‐0.95) for QFT reverters compared with LTBI. Purified protein derivative (PPD)‐specific CD4 + CD26 + IFN‐γ + cells were significantly increased (P = .0007) in QFT nonconverters compared with QFT converters at baseline. Conclusions Our results provide insight into the underlying mechanisms of resistance to sustained Mycobacterium tuberculosis infection.